Digital Literacy as a Strategic Solution to Overcome Fear of Missing Out Behavior - Chishomuddin, M Faiz; Putri, Elissa Hardian; Nugraheni, Shafa Alia; Dewi, Damajanti Kusuma (Proceedings of The International Conference on Psychology and Education, 2025)
The phenomenon of Fear of Missing Out (FoMO), which is increasingly rampant among Generation Z, impacts mental health and social well-being due to digital social pressure and social media addiction. This article aims to systematically examine the role of digital literacy as a strategic solution in addressing FoMO behavior. Using the Systematic Literature Review (SLR) method, this article explores findings from various selected studies over the past five years regarding the relationship between FoMO and Digital Literacy. The results indicate that enhancing digital literacy can help individuals filter information critically, manage their time effectively, and build awareness of the psychological risks of social media. Digital literacy has also proven to be effective in strengthening self-regulation skills and personal learning competence. Therefore, digital literacy is viewed not only as a long-term educational solution but also as a preventive approach in fostering a healthy digital culture, particularly for Generation Z.